Pathogenic and likely pathogenic variants in PALB2, CHEK2, and other known breast cancer susceptibility genes among 1054 BRCA‐negative Hispanics with breast cancer. Issue 16 (17th June 2019) - Weitzel, Jeffrey N.; Neuhausen, Susan L.; Adamson, Aaron; Tao, Shu; Ricker, Charité; Maoz, Asaf; Rosenblatt, Margalit; Nehoray, Bita; Sand, Sharon; Steele, Linda; Unzeitig, Gary; Feldman, Nancy; et al.
Abstract : Background: Breast cancer (BC) is the most common cancer and related cause of mortality among Hispanics, yet susceptibility has been understudied. BRCA1 and BRCA2 ( BRCA ) mutations explain less than one‐half of hereditary BC, and the proportion associated with other BC susceptibility genes is unknown. Methods: Germline DNA from 1054 BRCA ‐mutation–negative Hispanic women with hereditary BC (BC diagnosed at age <51 years, bilateral BC, breast and ovarian cancer, or BC diagnosed at ages 51‐70 years with ≥2 first‐degree or second‐degree relatives who had BC diagnosed at age <70 years), 312 local controls, and 887 multiethnic cohort controls was sequenced and analyzed for 12 known and suspected, high‐penetrance and moderate‐penetrance cancer susceptibility genes (ataxia telangiectasia mutated [ ATM ], breast cancer 1 interacting protein C‐terminal helicase 1 [ BRIP1 ], cadherin 1 [ CDH1 ], checkpoint kinase 2 [ CHEK2 ], nibrin [ NBN ], neurofibromatosis type 1 [ NF1 ], partner and localizer of BRCA2 [ PALB2 ], phosphatase and tensin homolog [ PTEN ], RAD51 paralog 3 [ RAD51C ], RAD51D, serine/threonine kinase 11 [ STK11 ], and TP53 ). Results: Forty‐nine (4.6%) pathogenic or likely pathogenic variants (PVs) in 47 of 1054 participants (4.5%), including 21 truncating frameshift, 20 missense, 5 nonsense, and 4 splice variants, were identified in CHEK2 (n = 20), PALB2 (n = 18), ATM (n = 5), TP53 (n = 3), BRIP1 (n = 2), and CDH1 and NF1 (both n = 1) and none were identified in NBN, PTEN, STK11, RAD51C, or RAD51D . Nine participants carried the PALB2 c.2167_2168del PV (0.85%), and 14 carried the CHEK2 c.707T>C PV (1.32%). Conclusions: Of 1054 BRCA ‐negative, high‐risk Hispanic women, 4.5% carried a PV in a cancer susceptibility gene, increasing understanding of hereditary BC in this population. Recurrent PVs in PALB2 and CHEK2 represented 47% (23 of 49) of the total, suggesting a founder effect. Accurate classification of variants was enabled by carefully controlling for ancestry and the increased identification of at‐risk Hispanics for screening and prevention. Abstract : Breast cancer (BC) is the most common cancer and related cause of mortality among Hispanics, yet BC susceptibility has been understudied. Whole‐exome sequencing was used to identify 50 (4.7%) pathogenic or likely pathogenic variants in 47 of 1054 (4.5%) BRCA ‐negative Hispanics with familial BC, including recurrent pathogenic variants in PALB2 and in CHEK2, where the classification was enabled by carefully controlling for ancestry.